Little neighbours in Hamburg: free-living aquatic flatworms (Platyhelminthes) - Yander L. Diez; Andreas Schmidt-Rhaesa (Evolutionary Systematics)
Free-living flatworms, also known as turbellarians, are abundant and key components of aquatic habitats. They play vital roles in food webs and contribute to ecosystem health. However, our understanding of their diversity remains limited, even from comparably well-studied regions of Europe. In this work, we summarise the available records on aquatic turbellarians from Hamburg, Germany, provide new records based on material obtained during exploratory collecting, and place selected species in a molecular phylogenetic context. We sampled four localities in Hamburg, two urban and two suburban, and three other localities in Germany and Switzerland, collecting submerged vegetation, litter, and mosses. Prior to our investigation, Hamburg had documented 26 species of aquatic turbellarians. Our collections have led to the first recorded instances of Stenostomum gotlandense and Castrella alba in Germany, along with four new species for Hamburg: Macrostomum rostratum, Microdalyellia schmidtii, Krumbachia hiemalis, and Polycelis tenuis. Additionally, we provide updated information for five species previously recorded from Hamburg: S. leucops, Prorhynchus stagnalis, Microdalyellia armigera, Gyratrix hermaphroditus, and Planaria torva. The phylogenetic analysis revealed cryptic diversity within S. grande and S. leucops, with S. grande comprising two distinct clades (Brazil and Japan + Germany), and S. leucops consisting of four clades (Sweden + Germany, two from Finland, and Brazil). One of the Finnish clades, S. leucops aquariorum, is both morphologically and molecularly distinct, and we recognise it as a valid species, now S. aquariorum. Future research is needed to further clarify the relationships of the remaining clades of these two species, particularly with material from their type localities in the United States. Among rhabdocoel microturbellarians, we identified cryptic diversity within Castrella truncata (with European and North American lineages) and Microdalyellia armigera (encompassing Finnish and Spanish lineages). We also provided the first molecular evidence supporting the monophyly of Krumbachia following the sequencing of K. hiemalis. Conversely, species of Bothromesostoma were found to be nested within a clade containing species of Mesostoma, leading us to propose synonymising these genera. Overall, our study underscores the rich biodiversity potential of urban and suburban ecosystems for detecting freshwater turbellarian species, while highlighting the need for further research in Hamburg and across Germany to clarify species distributions. Moreover, molecular phylogenetic analyses have uncovered cryptic diversity in several species of catenulids and rhabdocoels, emphasizing the importance of future efforts to describe potential new species.